PENGARUH LINGKUNGAN KERJA DAN INSENTIF TERHADAP KEPUASAN KERJA KARYAWAN UD. TRUBUS KOTA BEKASI - Viona Rezkiani; Amanda Setiorini (Jurnal Manajemen Bisnis Krisnadwipayana, 2023)
The purpose of this study was to analyze the effect of the work environment and incentives on UD job satisfaction. Bekasi City Trubus. This research uses quantitative descriptive methods. The population of this study was all UD employees. Trubus has 510 employees. The sample of this study amounted to 60 employees. The sampling technique is with the formula isaac and michael. The data collection technique is carried out by questionnaires. The data analysis techniques used are multiple and part partially ial linear regression analysis, The results of this study show: First, there is a positive and significant influence of the work environment on job satisfaction. Second, there isa positive influence of incentives on job satisfaction. Third, there is a positive influence of the work environment and incentives on job satisfaction. The results of this study are expected to be useful for increasing job satisfaction through a comfortable work environment and incentives provided.